Proteomic profiling of thyroid tissue in patients with obesity and benign diffuse goiter - Benabdelkamel, Hicham; Rafiullah, Mohamed; Masood, Afshan; Alsaif, Abdulaziz; Musambil, Mohthash; Alfadda, Assim A. (Frontiers in Endocrinology, 2022)
Goiter is a term which is used to describe the enlargement of the thyroid gland. The pathophysiology and molecular changes behind development of diffuse benign goiter remains unclear. The present study targeted to identify and describe the alterations in the thyroid tissue proteome from patients (obese euthyroid) with benign diffuse goiter (BDG) using proteomics approach. Thyroid tissue samples, from 7 age and sex matched, patients with BDG and 7 controls were obtained at the time of surgery. An untargeted proteomic analysis of the thyroid tissue was performed out utilizing matrix-assisted laser desorption/ionization time-of-flight mass spectrometry followed by two-dimensional difference in gel electrophoresis (2D-DIGE-MALDI TOF) for identification of the proteins. Progenesis software assessed changes in tissue proteins and found statistically significant differences in abundance in a total of 90 proteins, 46 up and 44 down (1.5-fold change, ANOVA, p 0.05) in BDG compared to the control group. Bioinformatic analysis identified dysregulation of signalling pathways linked to ERK1/2, Glutathione peroxidase and NADPH oxidase associated to organismal injury and abnormalities, endocrine system disorders and cancer. The thyroid tissue proteome in patients with BDG revealed a significant decrease in thyroglobulin along with dysregulation of glycolysis and an increase in prooxidant peroxidase enzymes. Dysregulation of metabolic pathways related to glycolysis, redox proteins, and the proteins associated with maintaining the cytoskeletal structure of the thyrocytes was also identified.